Derivation of cut‐offs for plasma neurofilament light in clinical routine using healthy subjects aged between 5‐90 - Simrén, Joel; Gobom, Johan; Andreasson, Ulf; Suárez‐Calvet, Marc; Depypere, Herman; Nyberg, Lars; Borroni, Barbara; Zetterberg, Henrik; Blennow, Kaj (Alzheimer's & dementia, 2022)
Background Plasma neurofilament light (NfL) is a dynamic and robust cross‐disease biomarker of neuroaxonal injury. However, to enable clinical introduction of the assay, establishing cut‐offs is crucial. Here, we sought to derive reliable cut‐offs by quantifying NfL in plasma in healthy individuals. Method Participants from eight cohorts of neurologically healthy participants spanning the ages of 5‐90 years were recruited. NfL was measured using commercial Quanterix® kits (Simoa® NF‐light Kit) on Simoa HD‐X or HD‐1 analyzers (Quanterix, Billerica, MA, USA). Age‐partitioned cut‐offs were determined at the 95th percentile, which was estimated using a rank‐based method. In addition, we introduced an internal calibrator (IC) to normalize values in‐between runs and a quality control (QC) system to ensure longitudinal stability of the assay in clinical routine. Result In total, we included 1724 (ages 5‐<18 years, n=27; 18‐<51, n=569; 51‐<61=614; 61‐<70, n=366; >70 150) individuals. Plasma NfL concentrations increased significantly with increasing age (r2 = 0.53, P < 0.001). We established the following age‐partitioned upper cut‐offs: <7 pg/mL in the group between ages 5‐17, <10 pg/mL for 18‐50, <15 pg/mL between 51‐60, <20 pg/mL between 61‐70, and <35 pg/mL for individuals >70 years. High and low QCs maintained coefficient of variation (CV) below 10%. Other laboratories seeking to introduce plasma NfL into clinical routine may send samples to achieve traceability to the data presented here. Conclusion To conclude, we established reference limits for plasma NfL across the lifespan. This will aid the introduction of plasma NfL into clinical routine, simplifying disease monitoring and diagnostics.